Magnetic resonance imaging‐quantified small bowel motility is a sensitive marker of response to medical therapy in Crohn's disease. Issue 3 (8th June 2015) - Plumb, A. A.; Menys, A.; Russo, E.; Prezzi, D.; Bhatnagar, G.; Vega, R.; Halligan, S.; Orchard, T. R.; Taylor, S. A.
Summary Background Magnetic resonance enterography (MRE) can measure small bowel motility, reduction in which reflects inflammatory burden in Crohn's Disease (CD). However, it is unknown if motility improves with successful treatment. Aim To determine if changes in segmental small bowel motility reflect response to anti‐TNFα therapy after induction and longer term. Methods A total of 46 patients (median 29 years, 19 females) underwent MRE before anti‐TNFα treatment; 35 identified retrospectively underwent repeat MRE after median 55 weeks of treatment and 11 recruited prospectively after median 12 weeks. Therapeutic response was defined by physician global assessment (retrospective group) or a ≥3 point drop in the Harvey–Bradshaw Index (prospective group), C‐reactive protein (CRP) and the MaRIA score. Two independent radiologists measured motility using an MRE image‐registration algorithm. We compared motility changes in responders and nonresponders using the Mann–Whitney test. Results Anti‐TNFα responders had significantly greater improvements in motility (median = 73.4% increase from baseline) than nonresponders (median = 25% reduction, P < 0.001). Improved MRI‐measured motility was 93.1% sensitive (95%CI: 78.0–98.1%) and 76.5% specific (95% CI: 52.7–90.4%) for anti‐TNFα response. Patients with CRP normalisation (<5 mg/L) had significantly greater improvements in motility (median = 73.4% increase) than those with persistently elevated CRP (median = 5.1%, P = 0.035). Individuals with post‐treatment MaRIA scores of <11 had greater motility improvements (median = 94.7% increase) than those with post‐treatment MaRIA score >11 (median 15.2% increase, P = 0.017). Conclusions Improved MRI‐measured small bowel motility accurately detects response to anti‐TNFα therapy for Crohn's disease, even as early as 12 weeks. Motility MRI may permit early identification of nonresponse to anti‐TNFα agents, allowing personalised treatment.